2014
DOI: 10.1007/s00442-014-3047-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for enhanced top-down control of freshwater macrophytes with nutrient enrichment

Abstract: The abundance of primary producers is controlled by bottom-up and top-down forces. Despite the fact that there is consensus that the abundance of freshwater macrophytes is strongly influenced by the availability of resources for plant growth, the importance of top-down control by vertebrate consumers is debated, because field studies yield contrasting results. We hypothesized that these bottom-up and top-down forces may interact, and that consumer impact on macrophyte abundance depends on the nutrient status o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 71 publications
4
33
1
Order By: Relevance
“…The hypothesis of Bakker & Nolet (2014) states that macrophyte food quality would be higher in eutrophic lakes and that omnivorous birds would therefore increase the proportion of macrophytes in their diets. In support of this hypothesis, we showed that along with P loading macrophyte C:P ratio decreases and bird impact increases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The hypothesis of Bakker & Nolet (2014) states that macrophyte food quality would be higher in eutrophic lakes and that omnivorous birds would therefore increase the proportion of macrophytes in their diets. In support of this hypothesis, we showed that along with P loading macrophyte C:P ratio decreases and bird impact increases.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas our modelling results are supporting the hypothesis, it remains to be tested under field conditions. Macrophyte nutrient concentrations increase upon fertilization and are more preferred food under experimental conditions for omnivorous ducks and fish (Dorenbosch & Bakker, 2011;Bakker & Nolet, 2014), but in the field, the relation between environmental and macrophyte nutrient concentrations is less clear (e.g. Casey & Downing, 1976).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrophytes in nutrient-enriched conditions are more palaTable 5.to birds (Bakker et al, 2014), and high bird density can reduce macrophyte development in eutrophic waters (Marklund et al, 2002). Although there are no counts of waterbird densities in the lower Vasse River, waterfowl were common during this study and the nearby Vasse-Wonnerup…”
Section: Macrophyte Establishmentmentioning
confidence: 69%